In vitro, in vivo, and clinical tests of a novel flexible ureteroscope for the diagnosis and treatment of kidney and ureteral diseases - Dai Hee Kim; Jung Hyun Shin; Se Young Choi; Dalsan You; Choung-Soo Kim; Hyung Keun Park (Investigative and Clinical Urology, 2018)
Purpose: Despite advances in flexible ureteroscopy, the high cost and long repair time of ureteroscopes limit their use in the urology. We compared the performance of a novel flexible ureteroscope (fURS) ‘HF-EH’ with that of the two contemporary fURSs ‘URF-P6’ and ‘COBRA’. Materials and Methods: We compared in vitro measurements of deflection angle, irrigation flow rate, and image quality between HF-EH and URF-P6 while also inspecting renal collecting systems in five female pigs. For clinical testing, we performed retrograde intrarenal surgeries using HF-EH in four patients. Experienced urologists compared performance parameters (irrigation, convenience, and maneuverability) between the HF-EH and COBRA. Results: The flow rate of HF-EH (21.0 mL/min) was worse, and its resolution (1.59 line pairs/mm) was inferior to that of URF-P6 (28.7 mL/min and 3.17 line pairs/mm, respectively). However, HF-EH was superior to URF-P6 in terms of loss of deflection angle with the insertion of accessories (1.8% vs. 12.7%). In vivo and clinical testing revealed that the performance parameters of HF-EH were slightly inferior to those of conventional domestic fURSs. We successfully performed retrograde intrarenal surgeries using HF-EH in four patients and achieved stone-free statuses in two. None of the patients exhibited any procedure-related complications. Conclusions: Although we observed that two of the three performance parameters of the novel ureteroscope ‘HF-EH’ were inferior to those of the conventional ureteroscope, we successfully used HF-EH to perform retrograde intrarenal surgeries in patients. Further studies on performance and durability are warranted for making HF-EH commercially available.